Convictions and signals in parliamentary speeches: Dáil Éireann debates on abortion in 2001 and 2013 - Baumann, Markus; Debus, Marc; Müller, Jochen (Irish political studies, 2015)
While party unity in legislative voting is generally high in parliamentary democracies, debates provide MPs with the opportunity to express political views even if they deviate from the party line. Using the extensive parliamentary debates on the reform of the Irish abortion legislation in 2001 and 2013, we assess whether Teachtaí Dála (TD) send signals to their constituents. In doing so, we take into account literature on the individual preference formation of political actors as well as institutional accounts that stress vote-seeking resulting from the electoral system. We also argue that personal characteristics like gender and family status should affect the positions of TDs on the abortion issue. In addition, we argue that the preferences of the constituents should particularly be taken into account by those TDs who only narrowly won a seat in the Dáil. Our analysis, which is based on a content analysis of all speeches held during the abortion reform debates in the Dáil in 2001 and 2013, provides support for our expectations.
Gesehen am 22.01.2018